Body composition as a predictor of chemotherapy-related toxicity in pancreatic cancer patients: A systematic review - Rizzo, Stefania; Scala, Isabel; Robayo, Angela Rodriguez; Cefalì, Marco; De Dosso, Sara; Cappio, Stefano; Xhepa, Genti; Del Grande, Filippo (Frontiers in Oncology, 2022)
Objectives: the objective of this systematic review was to assess associations between quantitative body composition measures extracted from imaging examinations and chemotherapy-related toxicity in pancreatic cancer patients. A secondary objective was to evaluate the different definitions of sarcopenia across included studies. Methods: This systematic review was conducted according to the PRISMA statement. A comprehensive literature search of three electronic databases was performed by two authors. For each eligible article, information was collected concerning the clinical setting; basic study; population characteristics; technical; body composition features evaluated; CA 19.9 tumor marker levels; chemotherapy drugs administered; toxicities (hematologic, nausea/vomiting, diarrhea, neuropathy, reduction of number of cycles, overall toxicity); association of body composition values with toxicities. The overall quality of the included studies was critically evaluated. Results: After the initial retrieval of 1137 articles, the systematic review included 12 articles (1/12 in the neo-adjuvant setting; 2/12 in the adjuvant setting; 3/12 in the metastatic setting; 2/12 in the unresectable setting; the other 4/12 included more than one clinical setting). The number of patients included ranged between 17 and 251; mean/median age ranged between 63 and 77 years; the percentage of sarcopenic patients ranged between 23 and 76%. The most frequent body composition parameter evaluated was skeletal muscle index (11/12). Chemotherapy regimens included gemcitabine (as monotherapy or in combination with other drugs); FOLFIRINOX and S-1. Among the trials including Gemcitabine, 2/9 demonstrated an association with toxicity, whereas 7/9 did not; among those including FOLFIRINOX, one demonstrated associated toxicity whereas the others did not. Altogether, 4/12 papers demonstrated an association between the body composition values and the development of chemotherapy-related toxicities. Conclusions: there is a wide variability of results about the association of body composition and chemotherapy-related toxicity in PC patients. Furthermore, cut-off values to define sarcopenia in PC patients are not yet uniformly defined.